Complete substitution of a secondary cell wall with a primary cell wall in Arabidopsis. (October 2018) - Sakamoto, Shingo; Somssich, Marc; Nakata, Miyuki; Unda, Faride; Atsuzawa, Kimie; Kaneko, Yasuko; Wang, Ting; Bågman, Anne-Maarit; Gaudinier, Allison; Yoshida, Kouki; Brady, Siobhan; Mansfield, Shawn; et al.
Abstract The bulk of a plant's biomass, termed secondary cell walls, accumulates in woody xylem tissues and is largely recalcitrant to biochemical degradation and saccharification1 . By contrast, primary cell walls, which are chemically distinct, flexible and generally unlignified2, are easier to deconstruct. Thus, engineering certain primary wall characteristics into xylem secondary walls would be interesting to readily exploit biomass for industrial processing. Here, we demonstrated that by expressing AP2/ERF transcription factors from group IIId and IIIe in xylem fibre cells of mutants lacking secondary walls, we could generate plants with thickened cell wall characteristics of primary cell walls in the place of secondary cell walls. These unique, newly formed walls displayed physicochemical and ultrastructural features consistent with primary walls and had gene expression profiles illustrative of primary wall synthesis. These data indicate that the group IIId and IIIe AP2/ERFs are transcription factors regulating primary cell wall deposition and could form the foundation for exchanging one cell wall type for another in plants. Plant primary and secondary cell walls have distinct features and functions. Now, scientists have successfully replaced the secondary cell wall inArabidopsis xylem fibres with a thick primary cell wall by specifically overexpressing AP2/ERF transcription factors.